Management of forest regeneration in boreal and temperate deer–forest systems: challenges, guidelines, and research gaps. Issue 10 (14th October 2016) - Beguin, Julien; Tremblay, Jean‐Pierre; Thiffault, Nelson; Pothier, David; Côté, Steeve D.
Abstract: Heavy browsing pressure from large ungulates is a multicontinent phenomenon that causes regeneration failure of many palatable tree species and induces important socioeconomic and ecological impacts in forest ecosystems. The development of forest management practices that address adequately this issue, however, remains scarce and challenging because (1) large herbivores are both a resource and a source of disturbance; (2) the management of forests and ungulate populations remains largely disconnected in practice; and (3) we still lack a good understanding of the role of critical factors, especially deer densities, vegetation attributes, and their interactions, on the magnitude of browsing damages on forest regeneration. We bring new insights into these challenging issues by critically reviewing the current methods used by managers and conservationists to mitigate deer impacts on forest regeneration, emphasizing the spatial scale at which these methods are undertaken. Specifically, we review management actions at multiple scales on both deer populations (e.g., hunting) and vegetation (e.g., silvicultural treatments) that are common to most deer–forest systems and, for that reason, deserve priority investigation. We identify strengths and limitations of current management actions and highlight the main research gaps. Based on this review, we propose a new integrated management scheme that explicitly addresses: (1) the integration and prioritization of management actions, (2) the development of adaptive management plans, and (3) the participation of stakeholders. Conflicting demands by different stakeholders have challenged the effectiveness of management strategies in deer–forest systems. To reverse this situation, we advocate for a shift of paradigm and the development of integrated strategies that (1) bridge the gap between management actions and the design of in situ experiments and (2) coordinate actions at multiple spatial scales on both deer populations and forests. We propose a new framework informed by key objectives and grounded in the adaptive management paradigm to support this transition, and suggest a research agenda for the next decade(s).